Pretreatment Predictors of Response to PegIFN-RBV Therapy in Egyptian Patients with HCV Genotype 4. - Hanan H Rizk; Nadia M Hamdy; Nadia L Al-Ansari; Hala O El-Mesallamy (PLoS ONE, 2016)
BACKGROUND:Egypt has the highest prevalence of a difficult to treat chronic hepatitis C virus (HCV), genotype 4. Pretreatment factors could guide individualization of therapy which aids in treatment optimization and interleukin IL28B gene polymorphism has been shown to closely relate to HCV treatment response. Polymorphisms in genes encoding inhibitors of T-cell response, which have role in disease progression as Programmed Cell Death 1 (PD-1), and Cytotoxic T-Lymphocytes Antigen-4 (CTLA-4), could be candidate markers predicting treatment response. METHODS:This cohort study consisted of 200 chronic HCV genotype 4 infected patients treated with PegIFN α-2a and RBV in 2 hepatology centers. Genotyping of the polymorphisms in the IL28B gene region (rs12979860), PD1.3 (rs11568821) and CTLA-4 (rs231775) was performed on DNA collected from each patient using TaqMan® genotyping assay. Groups were classified according to response into sustained virological responders (SVR), or non-responders (NR). A multivariate logistic regression analysis was used to identify potential markers, host pretreatment clinical and viral predictive factors including viral load, insulin resistance, and alpha fetoprotein (AFP) related to treatment response. RESULTS:Our results showed that in a multivariate analyses IL28B C/C genotype was the most significant predictor for SVR (OR = 10.86; p<0.0001) followed by AFP (OR = 0.915; p = 0.001) then CTLA-4/G genotypes (OR = 1.948; p = 0.022). However, PD-1.3/A genotypes and platelets count were significantly related to response in univariate analysis only (OR = 1.973; p = 0.023; OR = 1.007; p = 0.009 respectively). CONCLUSION:IL28B SNP, AFP level, and CTLA-4 SNP could be used in conjunction to predict treatment response in HCV genotype 4 infected Egyptian patients.